Love beyond religious conviction: the challenges of interreligious marriage in South Wollo, Ethiopia - Muluneh Animut Tilahun; Mellese Madda Gatisso; Abdu Muhammed Ali (Discover Global Society)
Abstract Although interreligious marriages between Muslims and Orthodox Christians in South Wollo have fostered social integration and peaceful coexistence for centuries, basic theological differences, various cultural and social factors, and recent religious reform movements pose challenges for couples and their children. This study aims to explore the challenges of interreligious marriage practices and the impacts of recent religious reform movements in South Wollo. To achieve this objective, the researchers employed a phenomenological study design and collected primary data through in-depth interviews and focus group discussions from interreligious couples and their children, local elders, religious fathers, and other community members. The study reveals that interreligious marriages pose significant challenges on interreligious couples and their children due to theological and cultural differences, pressures from families and relatives, social stigma and exclusion from different socio-cultural activities. Besides, economic difficulties to celebrate both religion holidays and disagreements in deciding the religious upbringing of their children further intensified their struggles. In addition, the recent religious reform movements, particularly Salafism in Islam and Mahibere Kidusan within Orthodox Christianity, have affected South Wollo’s historically syncretic religious culture. Thus, this study highlights how recent religious reform movements are reshaping South Wollo’s harmonious interreligious landscape, intensifying the challenges faced by interreligious couples and contributing to the decline of interreligious marriage practices. As a result, there is an urgent need for community leaders, religious institutions, and policymakers to work together to preserve South Wollo’s tradition of peaceful interreligious coexistence and to address the rising challenges posed by recent religious reform movements.